1980
DOI: 10.1099/00221287-117-1-57
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Effects on Germ-free Mice of Association with Several Strains of Anaerobic Bacteria

Abstract: The effects of the following changes throughout the association of germ-free mice with increasing numbers of anaerobic bacteria were studied: (i) elution patterns obtained by gel-filtration chromatography of caecal diffusates; (ii) concentration of beta-aspartylglycine in caecal and faecal contents; (iii) polypeptide patterns obtained by sodium dodecyl sulphate-polyacrylamide gel electrophoresis of caecal supernatants; (iv) free amino acid content of caecal supernatants; (v) faecal bile acids, analysed by gas-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
1

Year Published

1981
1981
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 10 publications
(11 reference statements)
0
26
1
Order By: Relevance
“…As stated before, these capabilities seem to be a rare event among intestinal micro-organisms (6,14,15).…”
Section: Discussionmentioning
confidence: 99%
“…As stated before, these capabilities seem to be a rare event among intestinal micro-organisms (6,14,15).…”
Section: Discussionmentioning
confidence: 99%
“…In earlier studies we tried to 'normalize' germ-free mice with cultured microfloras (Welling, Groen, Tuinte, Koopman & Kennis, 1980;. So far we have not succeeded in achieving this goal.…”
mentioning
confidence: 99%
“…The resistance of the normal host to the implantation of exogenous microorganisms has been termed "colonization resistance" (34). Some studies with animals have suggested that this protective effect is related to the anaerobic component of the intestinal microflora (21,(34)(35)(36), whereas others have pointed to facultative gram-negative rods as important in this regard (7,14,15,19). However, to our knowledge, there are no data to prove that colonization resistance occurs in humans or, if it does occur, to indicate to which component of the intestinal microflora it is related.…”
mentioning
confidence: 99%